2010
DOI: 10.1002/aqc.1090
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ecological changes in and around marine reserves using community perceptions and biological surveys

Abstract: ABSTRACT1. Well-enforced partial or total no-fishing zones (collectively known as marine protected areas, or MPAs) can help restore degraded coral reefs and enhance fish populations.2. A comparison was made of community perceptions of ecological changes in an MPA with concurrent scientific data on these changes in the same MPA. Such analyses are particularly important in community-based MPAs where local support is a key determinant of ecological success.3. The no-take MPA in question was initially launched in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…similar coral cover or fish abundance) compared with open access (Fig. 10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54].…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…similar coral cover or fish abundance) compared with open access (Fig. 10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54].…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
“…Only 16 studies reported enough baseline data [36,40,41,44,46,47,51,55,56] and these were classified into poor, fair and good conditions (Fig. 12).…”
Section: Resource Baseline Condition As a Contextual Factormentioning
confidence: 99%
See 1 more Smart Citation
“…This has left many municipalities without mooring buoys to define marine reserve boundaries, patrol boats, fuel to conduct regular patrols, guardhouses, or properly trained enforcement personnel [46]. Furthermore, weak coordination between stakeholders has resulted in the inability of municipalities to enforce municipal laws, which has reduced the effectiveness of interventions [47,48]. Decentralization has also created challenges for management because municipal boundaries define jurisdictional boundaries, which do not correspond to resource boundaries that can exist between, beyond, or within multiple municipalities, thereby restricting effective ecosystem-based conservation [47,49].…”
Section: Governance Frameworkmentioning
confidence: 99%
“…Walmsley, Medley & Howard, 2005). It is necessary to acknowledge memory biases that may be present (Table 1; Daw, 2010) and consider the motivations of respondents to over-or underreport (reviewed by Yasu´e, Kaufman & Vincent, 2010). Comparing multiple sources of local knowledge ('local' data-collection methods reviewed by Danielsen, Burgess & Balmford, 2005) with scientific observations can help determine the strengths and weaknesses of both approaches.…”
mentioning
confidence: 99%